(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The article provides information on the origin, distribution, biological properties, history of use in the world population, medicinal properties and technology of growing the medicinal plant monarda (Monarda dydyama L). The article gives advice on how to use the plant.